Headache and Symptoms of Temporomandibular Disorder: An Epidemiological Study - Goncalves, Daniela A. G. [UNESP]; Bigal, Marcelo E.; Jales, Luciana C. F.; Camparis, Cinara Maria [UNESP]; Speciali, Jose G. (Wiley-Blackwell Publishing, Inc, 2010)
Objectives.-A population-based cross-sectional study was conducted to estimate the prevalence of migraine, episodic tension-type headaches (ETTH), and chronic daily headaches (CDH), as well as the presence of symptoms of temporomandibular disorders (TMD) in the adult population.Background.-The potential comorbidity of headache syndromes and TMD has been established mostly based on clinic-based studies.Methods.-A representative sample of 1230 inhabitants (51.5% women) was interviewed by a validated phone survey. TMD symptoms were assessed through 5 questions, as recommended by the American Academy of Orofacial Pain, in an attempt to classify possible TMD. Primary headaches were diagnosed based on the International Classification of Headache Disorders.Results.-When at least 1 TMD symptom was reported, any headache happened in 56.5% vs 31.9% (P < .0001) in those with no symptoms. For 2 symptoms, figures were 65.1% vs 36.3% (P < .0001); for 3 or more symptoms, the difference was even more pronounced: 72.8% vs 37.9%. (P < .0001). Taking individuals without headache as the reference, the prevalence of at least 1 TMD symptom was increased in ETTH (prevalence ratio = 1.48, 95% confidence interval = 1.20-1.79), migraine (2.10, 1.80-2.47) and CDH (2.41, 1.84-3.17). At least 2 TMD symptoms also happened more frequently in migraine (4.4, 3.0-6.3), CDH (3.4; 1.5-7.6), and ETTH (2.1; 1.3-3.2), relative to individuals with no headaches. Finally, 3 or more TMD symptoms were also more common in migraine (6.2; 3.8-10.2) than in no headaches. Differences were significant for ETTH (2.7 1.5-4.8), and were numerically but not significant for CDH (2.3; 0.66-8.04).Conclusions.-Temporomandibular disorder symptoms are more common in migraine, ETTH, and CDH relative to individuals without headache. Magnitude of association is higher for migraine. Future studies should clarify the nature of the relationship.
Keywords: epidemiology; temporomandibular joint; prevalence; primary headaches; migraine